Epidermal growth factor receptor intron-1 CA repeat polymorphism on protein expression and clinical outcome in Taiwanese oral squamous cell carcinoma - Shiang-Fu Huang (Nature Portfolio, 2017)
Abstract This study was designed to explore the relationship between epidermal growth factor receptor (EGFR) CA repeats polymorphism and protein expression in oral cavity squamous cell carcinoma (OSCC). A total of 194 OSCCs were examined for EGFR protein overexpression, gene copy number and the length of their CA repeats. The length of the EGFR CA repeats was found not to be associated with EGFR gene copy number or with protein overexpression. To exclude the effect of EGFR gene copy number on protein overexpression, only those OSCC tumors with disomy of the EGFR gene were included in further analysis. In this subgroup, EGFR protein overexpression was significantly associated with poor differentiation of the tumor cells and lymph node metastasis, especially extra-capsular spread. However, EGFR CA repeats were not related to any clinicopathological factor. Interestingly, patients genetically found to have the EGFR CA repeats SS genotype and having tumors with EGFR protein overexpression were found to have a worst prognosis in terms of disease-free survival (DFS) (HR = 2.68; 95% CI, 1.03–6.98) after multivariate adjustment. The present study demonstrates that concurrent overexpression of EGFR protein in the presence genetically of the SS form CA repeats acts as a predictor for poor DFS.